Leucine levels in low protein diets for pigs in the initial phase - Huepa, Laura Marcela Diaz; Fachinello, Marcelise Regina; Esteves, Lucas Antônio; De Paula, Vinicius Ricardo Cambito [UNESP]; Ferreira, Silvia Leticia [UNESP]; Pasquetti, Tiago; Castilha, Leandro Dalcin; De Souza Vasconcellos, Ricardo; Pozza, Paulo Cesar (Universidade Estadual de Londrina, 2017)
The objective of this study was to evaluate the standardized ileal digestible (SID) leucine levels in low crude protein diets on Performance, backfat thickness, longissimus dorsi depth and biochemical blood parameters of starting pigs. A total of 50 pigs, with initial weight of 11.14±0.24 kg; were distributed in a randomized blocks design with five treatments (1.10; 1.25; 1.40; 1.55 and 1.70% SID leucine), five replicates and two animals per experimental unit, comprised for a barrow and a gilt. The feed conversion ratio (FCR) reduced (P=0.018) due to the increasing SID leucine levels, without affecting other growth performance parameters (final weight, average daily feed intake, average daily gain, backfat thickness, longissimus dorsi depth and lean meat percentage). There was a quadratic effect for plasma triglyceride (P=0.049) and plasma urea (P=0.001). The optimal SID leucine levels obtained for triglycerides and urea were 1.16% and 1.24%, respectively, by associating the quadratic model with the Linear Response Plateu. Low crude protein diets with SID leucine levels up to 1.70% improved the feed conversion with desired urea and triglycerides concentration in blood plasma achieved at 1.16% and 1.24%, respectively.
Keywords: Antagonism; Blood parameters; Branched chain amino acids; Performance